Literature Analysis on the Role of Technology in Economic Growth - Siska Simamora (SEAN Institute, 2024)
Innovation-based economy has become a major driver of economic growth in various countries. Innovation, especially in the form of technological advancement, contributes to increased productivity, efficiency, and global competitiveness. This study is a literature analysis that explores the relationship between technology and economic growth, by reviewing previous studies that discuss the impact of innovation on the industrial sector, workforce, and economic policy. The results of the review show that the application of digital technology, automation, and artificial intelligence play a significant role in creating a more dynamic and adaptive economic model. In addition, investment in research and development (R&D) and policies that support the innovation ecosystem are key factors in driving sustainable economic growth. However, challenges such as the technology gap and human resource readiness are still obstacles in the implementation of an innovation-based economy. This study is expected to provide insight for policy makers and academics in developing economic strategies based on technological innovation.